Synthesis, crystal structure and luminescence studies of zinc(ii) and cadmium(ii) complexes with 6-(1H-tetrazol-5-yl)-2-naphthoic acid. Issue 34 (21st July 2016) - Chen, Xi; Zhang, Biquan; Yu, Fan; Su, Min; Qin, Wenming; Li, Bao; Zhuang, Gui-lin; Zhang, Tianle
Abstract : Two coordination polymers have been synthesized and structurally characterized, which exhibit different luminescent properties caused by the different coordination environments of the metal ions. Abstract : Two coordination polymers (CPs) with a novel bifunctional ligand, [ZnL] n (1 ) and [CdL(H2 O)] n (2 ), (L = rigid 6-(1 H -tetrazol-5-yl)-2-naphthoic acid), have been synthesized and structurally characterized, which reveal that the two constructed CPs exhibit three dimensional structures. The two CPs consist of a one-dimensional Zn-tetrazole chain and a double-layered two-dimensional Cd-tetrazole structure. In addition, IR, elemental analysis, and luminescent spectra of1 and2 were also examined. At room temperature, 1 exhibits an intense emission at around 421 nm upon 370 nm excitation, whereas2 exhibits an intense emission at 381 nm upon 350 nm excitation. Through variable-temperature luminescent and quantum calculations, the blue-shift of the peaks from the ligand and1 and2 is ascribed to the different configurations of L caused by the different coordination environments of the metal ions.